Topical delivery into skin using SPACE peptides - Nurfitriah Ismail (2015)
In recent decades, various methods including particulate control release systems have been employed to protect nucleic acid therapeutics (NATs) against degradation as well as overcoming the stratum corneum but were not efficient enough due to lack of elasticity. Application of ultradeformable liposomes is a promising approach for improving drug penetration and delivery efficiency. Ultradeformable liposomes are capable of demonstrating deformability during pore penetration. On the other hand, by conjugating nanoparticles with skin penetrating and cell entering (SPACE) peptides, the penetration into skin and cell entering can be facilitated, considerably. In this study, SPACE peptides were conjugated to ultradeformable liposomes composed of Phospholipon 90g (P90G) and cholesterol encapsulating calcein as model drug. Lipid hydration method via rotary evaporator was used for synthesis of liposomes. Nanoparticles were characterized in terms of size, size distribution and ζ - potential. Entrapment efficiency was 66 ± 9.5% and in vitro skin permeation confirmed the capability of the system in increasing topical penetration across the SC. Different ratios of P90G/cholesterol were tried in achieving sustained release and increased cellular uptake and transfection into 3T3 cells. Overall, the system showed promising capabilities for NATs delivery to skin.